1990
DOI: 10.1126/science.2326646
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Coat Protein Neurotoxicity Prevented by Calcium Channel Antagonists

Abstract: Coat protein gp120 from the human immunodeficiency virus type-1 (HIV-1) increased intracellular free calcium and injured rodent retinal ganglion cells and hippocampal neurons in culture. Highly purified recombinant gp120 envelope protein produced these effects in a dose-dependent fashion at picomolar concentrations. Immunoprecipitation with antibody to gp120, but not with control immunoglobulin-containing serum, depleted solutions of the viral envelope protein and also prevented both the rise in intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
296
2
3

Year Published

1991
1991
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 586 publications
(313 citation statements)
references
References 35 publications
12
296
2
3
Order By: Relevance
“…Recent reports on the neurotoxicity of gp 120 in cell culture suggested that signal transduction through an unknown surface molecule may disturb cellular tunetians by raising intracellular Ca 2 + concentrations ( Brenneman et al, 1988;Dreyer et al, 1990;Kaiser et al, 1990;Pulliam et al, 1991 ). When we measured intracellular Ca 2 + concentrations in D-54 cells in response to 0.01 to 1 J.Lg/ml rgp120, no increase of Ca 2 + Ieveis could be detected (Fig.…”
Section: Determination Of Intracellular Calcium Concentrationsmentioning
confidence: 73%
See 3 more Smart Citations
“…Recent reports on the neurotoxicity of gp 120 in cell culture suggested that signal transduction through an unknown surface molecule may disturb cellular tunetians by raising intracellular Ca 2 + concentrations ( Brenneman et al, 1988;Dreyer et al, 1990;Kaiser et al, 1990;Pulliam et al, 1991 ). When we measured intracellular Ca 2 + concentrations in D-54 cells in response to 0.01 to 1 J.Lg/ml rgp120, no increase of Ca 2 + Ieveis could be detected (Fig.…”
Section: Determination Of Intracellular Calcium Concentrationsmentioning
confidence: 73%
“…ln AIDS patients, this mechanism has been suggested to be responsible forT helper cell depletion (Ameisen and Caprone, 1 991) and could also cause cellular dysfunction and atrophy as observed in the brain (Fauci, 1988). ln addition, the HIV envelope glycoprotein gp 120 has been shown to increase intracellular Ca 2 + concentrations tagether with NMDA receptor agonists and to injure rodent neurons in vitro (Brenneman et al, 1988;Dreyer et al, 1990;Lipton et al, 1991 ). These mechanisms and the observed tyrosine phosphorylation in response to rgp120 in glial cells could provide a combination of signals leading to astrocytosis, impairment of myelin, and neurodegeneration as found in brains of AIDS patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This neuronal damage is thought to be predominantly indirect, resulting from the stimulation of macrophages and subsequent release of toxins (9,11,12). The neurotoxic effects of gp120 were demonstrated both in primary rodent and human neuronal cultures and in a gp120-transgenic mouse model (13)(14)(15)(16)(17)(18)(19)(20)(21). Previous studies in our laboratory and in others demonstrated that picomolar concentrations of gp120 cause a dramatic increase in the ability of glutamate to increase intracellular calcium levels and consequent neuronal damage in an "excitotoxic," N-methyl-D-aspartate (NMDA) receptor-mediated fashion (14 -19).…”
mentioning
confidence: 95%